INTERNSHIP TRAINING PROGRAMS. - Thompson, David W. (The Accounting Review, 1950)
Internship training in accounting is not a recent development. Several schools have had such programs in successful operation since the middle thirties. Cooperative training programs with industrial organizations, although not on as broad a scale, have been in existence for many years. Many employers view an internship program as a situation where they obtain part-time help to assist them in a busy season or during periods when regular employees are on vacation. They consider their part of the program merely to give the trainee a place to work and to pay him the usual rate for work of the type performed. The trainee learns only what he is able to observe. Firms of this nature should be avoided for internships. An internship program will place extra responsibilities and work on the employer but there are advantages to him that more than compensate for this additional trouble. In summary, the main points can be stated as: (1)Internship training programs have definite advantages to the student, to the cooperating business organization, and to the school. (2) There are no real disadvantages connected with internship training. Most of the difficulties encountered are the result of (a) poor selection of participants, (b) inadequate planning on the part of the school and the cooperating business, and (c) insufficient supervision and follow- through. (3) Internship training programs will require more work from the student, the representative of the cooperating business, and the university faculty. The results are well worth the added trouble. (4) Industrial internships have great merit and should receive increased attention from educators and industry.